Effect of calcifying bacteria on permeation properties of concrete structures - Achal, V.; Mukherjee, Abhijit; Reddy, M. (Han'gug Mi'saengmul Saengmyeong Gong Haghoe, 2010)
Microbially enhanced calcite precipitation on concrete or mortar has become an important area of research regarding construction materials. This study examined the effect of calcite precipitation induced by Sporosarcina pasteurii (Bp M-3) on parameters affecting the durability of concrete or mortar. An inexpensive industrial waste, corn steep liquor (CSL), from starch industry was used as nutrient source for the growth of bacteria and calcite production, and the results obtained with CSL were compared with those of the standard commercial medium. Bacterial deposition of a layer of calcite on the surface of the specimens resulted in substantial decrease of water uptake, permeability, and chloride penetration compared with control specimens without bacteria. The results obtained with CSL medium were comparable to those obtained with standard medium, indicating the economization of the biocalcification process. The results suggest that calcifying bacteria play an important role in enhancing the durability of concrete structures.